A Small Guanosine Triphosphate Binding Protein PagRabE1b Promotes Xylem Development in Poplar - Liu, Ying-Li; Wang, Li-Juan; Li, Yu; Guo, Ying-Hua; Cao, Yuan; Zhao, Shu-Tang (Frontiers in Plant Science, 2021)
Rab GTPases comprised the largest family of the small guanosine triphosphate (GTP)-binding proteins which regulate various biological processes. Recent studies have found that plant Rabs plays some specific functions. However, the functions of Rabs in wood development in trees remain unknown. In this study, functional characterization of PagRabE1b in Populus was performed. Quantitative RT-PCR analysis revealed that PagRabE1b was highly expressed in stems, especially in phloem and xylem tissues. Overexpression of PagRabE1b (PagRabE1b-OE) in poplar promoted programmed cell death, and increased growth rate and secondary cell wall thickness. Quantitative analysis of monosaccharide content showed that various monosaccharides were significantly increased in secondary xylem tissues of the overexpressed lines. Flow cytometry analysis showed that the number of apoptotic cells in PagRabE1b-OE lines are more than wild type, which indicated PagRabE1b may play a role in programmed cell death. Further studies revealed that constitutive expression of PagRabE1b up-regulated the expression of genes involved in secondary cell wall biosynthesis, programmed cell death and autophagy. Collectively, our results suggest that PagRabE1b plays a positive role in promoting the xylem development of poplar.